Analysis of Low-Stiffness-Resilient-Shaft (LSRS) for Semi-Active-Title of thesis Steering (SAS) System - HUSSAIN, NAJAF (2017)
The use of the Low-Stiffness-Resilient-Shaft (LSRS) in the Semi-Active-Steering (SAS) system helps remove the drawbacks of the conventional and Steer-By-Wire (SBW) systems.